PENERAPAN SUPER ENKRIPSI HILL CIPHER DAN RSA UNTUK PENGAMANAN DATA FILE AUDIO MP3 - Hakim, Azizhil; Zhya Anggraini; Dilla Sillfani; Renika Ayuni; Fauzi, Achmad (Jurnal Sistem Informasi Kaputama (JSIK), 2025)
Digital data security, especially audio files, is a major issue in the modern era, especially with the increasing risk of hacking and file tapping. To protect audio files such as MP3 format, this study suggests a combination of Hill Cipher and RSA algorithms for the Super Encryption method. Hill Cipher uses a linear matrix to encrypt data at high speed, while RSA uses a symmetric key created by Hill cipher to encrypt. The combination of these two algorithms produces a strong double layer of security to protect audio files. The layered encryption process uses Hill Cipher as the initial stage before using RSA for additional security. This super encryption is very good for maintaining data confidentiality. This study helps develop a digital data security system based on cryptography with a focus on audio files. This method can be used for various things, such as maintaining sensitive voice communications, maintaining important recordings, and creating applications based on audio data. However, further development can be done to improve the scalability and efficiency of this method, especially for large audio data files or data in the form of.